(Communication Barriers between Tutors and Learners in the Package C Program at the Lestari Hutuo Community Learning Activity Center) - Hasan, Cikitha Feblistya Is; Subhan, Andi; Ratnasari, Dwi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to find the communication barriers between tutors and community learners in the C Package Program at Pkbm Hutuo Lestari. The method used in this study is through a descriptive-qualitative approach. In this study, informants are taken among tutors by purposeful sampling and among community learners through convenience sampling. The data collection technique is by observation, interview, and documentation. The results of this study indicate that in the Package C program at the Hutuo Lestari Community Learning Center, there are several communication barriers during the teaching and learning process, namely physical, physiological, psychological, and semantic barriers. Specifically, the main obstacle is the semantic barrier. Some tutors and community learners are from different regions with different mother tongues, so it is difficult to understand each other's messages.